Deletion of Mir223 Exacerbates Lupus Nephritis by Targeting S1pr1 in Faslpr/lpr Mice - Hiramatsu-Asano, Sumie; Sunahori-Watanabe, Katsue; Zeggar, Sonia; Katsuyama, Eri; Mukai, Tomoyuki; Morita, Yoshitaka; Wada, Jun (Frontiers in Immunology, 2021)
Objective: The micro RNAs (miRNAs) and their target mRNAs are differentially expressed in various immune-mediated cells. Here, we investigated the role of Mir223 and sphingosine-1-phosphate receptor 1 (S1pr1) in the pathogenesis of systemic lupus erythematosus. Methods: We analyzed miRNA and mRNA profiling data of CD4+ splenic T cells derived from MRL/MpJ-Faslpr/J mice. We performed 3’ untranslated region (UTR) luciferase reporter gene assay using human umbilical vein endothelial cells (HUVEC). We generated the B6-Mir223-/-Faslpr/lpr mice and the lupus phenotypes were analyzed. Results: In CD4+ splenic T cells, we identified upregulation of miR-223-3p and downregulation of the possible target, S1pr1 by RNA sequencing of MRL/MpJ-Faslpr/J mice. The transfection with miR-223-3p mimic significantly suppressed a luciferase activity in HUVEC treated with a Lentivirus vector containing 3’ UTR of S1pr1. The mRNA levels of S1pr1 were significantly decreased after miR-223-3p overexpression. In B6-Mir223-/-Faslpr/lpr mice, the proportion of CD3+ T cells, CD3+CD4-CD8- cells, B cells, plasma cells, and S1PR1+CD4+ T cells in the spleen was significantly increased compared with that in B6-Mir223+/+Faslpr/lpr mice by flow cytometry. B6-Mir223-/-Faslpr/lpr mice demonstrated the elevation of glomerular and renal vascular scores associated with enhanced intraglomerular infiltration of S1PR1+CD4+ T cells. Conclusion: Unexpectedly, the deletion of Mir223 exacerbated the lupus phenotypes associated with increased population of S1PR1+CD4+ T in spleen and the enhanced infiltration of S1PR1+CD4+ T cells in inflamed kidney tissues, suggesting compensatory role of Mir223 in the pathogenesis of lupus nephritis.